2021
DOI: 10.3389/fphar.2021.750165
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Genus Sanguisorba: Traditional Uses, Chemical Constituents and Medical Applications

Abstract: Genus Sanguisorba (family: Rosaceae) comprises nearly 148 species, distributed widely across the temperate and subtropical regions of the Northern Hemisphere. Sanguisorba officinalis L. (S. officinalis) has been used as a hemostatic and scald treating medicine in China for a long time. Numerous studies have demonstrated that plant extracts or monomers from S. officinalis exhibit several pharmacological effects, such as anti-cancer, anti-virus, anti-inflammation, anti-bacteria, neuroprotective and hepatoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 134 publications
0
45
0
Order By: Relevance
“…In addition, in order to observe the effect of drugs on the healing of DW more directly and accurately, and to minimize the impact of animal heterogeneity, we constructed two wounds on the backs of diabetic rats, one for ESO treatment and the other for vehicle (PBS) treatment, which would have prevented us from detecting the effects of ESO on liver and renal function. Although S. officinalis L. is a common component of the Mediterranean diet with few toxic and side effects (Zhou et al, 2021), and it has accelerated the repair of DW, diabetic rats exhibited no obvious mental and activity abnormalities following ESO treatment; however, a systematic evaluation of systemic toxicity will strengthen the article. This is what is missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in order to observe the effect of drugs on the healing of DW more directly and accurately, and to minimize the impact of animal heterogeneity, we constructed two wounds on the backs of diabetic rats, one for ESO treatment and the other for vehicle (PBS) treatment, which would have prevented us from detecting the effects of ESO on liver and renal function. Although S. officinalis L. is a common component of the Mediterranean diet with few toxic and side effects (Zhou et al, 2021), and it has accelerated the repair of DW, diabetic rats exhibited no obvious mental and activity abnormalities following ESO treatment; however, a systematic evaluation of systemic toxicity will strengthen the article. This is what is missing.…”
Section: Discussionmentioning
confidence: 99%
“…S. officinalis L. is a traditional Chinese medicine used to treat skin injuries in China. In addition, recent pharmacological studies have shown that S. officinalis L. offers a variety of health benefits, including anti‐inflammatory, anti‐infectious, anti‐allergic, and anti‐oxidant properties (Yasueda et al, 2020; Zhou et al, 2021). However, no prior publication has described its use in DW.…”
Section: Introductionmentioning
confidence: 99%
“…S·officinalis is called Di-Yu in China, Zi-Yu in South Korea and Japan, and Burnet in Western nations. Sanguisorbae Radix, the dried root of Sanguisorba officinalis L. or Sanguisorba officinalis var, is traditionally used to cool blood, clear heat and heal wounds [ 46 ]. Studies have shown that in the absence of exogenous IL-3, a concentration of Di-Yu saponins (DYS) higher than 20 mg/L can promote the differentiation and maturation of megakaryocytes, and DYS up-regulates the expression of IL-3R in megakaryocytes [ 47 ].…”
Section: Effects Of Phytochemicals On Megakaryocyte Differentiationmentioning
confidence: 99%
“…Current studies have shown that TCMs, including Cremastra appendiculata ( Wang et al, 2021 ), Artemisia Annua ( Zhang S. Q et al, 2020 ) and Rhodiola rosea L. ( Zhang S. Q et al, 2020 ), can be used as candidate drugs against NSCLC. Sanguisorba officinalis L. (SOL) is a medicinal plant widely distributed in China ( Zhou et al, 2021 ). Currently, “Diyu Sheng Bai Pian,” made from SOL, is used clinically to treat leukopenia induced by antitumor drugs ( Zhao, 2019 ).…”
Section: Introductionmentioning
confidence: 99%